INTEGRATING DIGITAL TECHNOLOGIES TO ENHANCE CSR STRATEGIES FOR RETAIL COMPANIES IN LATVIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
As sustainable practices grow in importance, Latvian companies must align their CSR strategies with environmental goals. Integrating digital technologies into CSR presents an opportunity for progress, innovation, and efficiency. Through this transformation, companies can benefit both themselves and the environment, reducing their ecological footprint and contributing to a sustainable future. Embracing this evolution in CSR demonstrates commitment to positive change and fosters collaboration among stakeholders. By combining sustainable practices with digital technologies, Latvian companies can lead in creating a greener business landscape. Adaptation and improvement of CSR strategies can make a lasting global impact on sustainable development. The goal of the research was to assess the ways in which retail companies in Latvia can utilize digital technologies to enhance their CSR strategies, with an emphasis on advocating for sustainable practices. To reach the goal the following tasks were set forth: (1) to research theoretical sources on CSR and digitalization, with a particular accent upon retail companies; (2) to work out empirical research methodology; (3) to carry out empirical research and interpret results. The main empirical research method employed was the online survey of retail customers (n=207). The findings suggest that digital technologies play a crucial role in improving companies' CSR capabilities. The findings show that opinions about the role of digital technology in CSR vary greatly depending on age and gender. Younger people, especially women, are very supportive of using digital tools in CSR, possibly because they are more familiar with technology and have a stronger awareness of environmental issues. On the other hand, the responses from older age groups show a mix of opinions, indicating the need for specific awareness campaigns and training to bridge the confidence gap. To effectively incorporate digital technologies into CSR efforts, retail companies need to customize their strategies to accommodate these demographic differences to promote widespread and inclusive adoption.